Parental impact on children living with autism spectrum disorder at the University College Hospital (UCH) Ibadan, Nigeria (2022)
Parenting is a problem affecting the well-being of children with autism spectrum disorder in Nigeria. Previous studies on subjective wellbeing had focused on school and environmental factors. This paper investigated parental impact on wellbeing of children with autism at the University College Hospital Ibadan. The study adopted a descriptive survey research design. A purposive sampling technique was used to select 55 parents of children (caregivers) with autism spectrum disorders as respondents. A structured questionnaire titled "Parental Impact and Autism Spectrum Disorder Questionnaire (PIASDQ) was used to elicit responses and data were analysed using Pearson Product Moment Correlation (PPMC) and Regression Analysis tested at 0.05 alpha level. There is a significant positive relationship between parental impact and psychological wellbeing of children with autism disorder (r = .811, n= 55, P(.001) < 0.05), there is a significant positive relationship between parental impact and health wellbeing of children with autism disorder (r = .717, n= 55, P(.003) < 0.05), there is a significant positive relationship between parental impact and social wellbeing of children with autism disorder (r = .724, n= 55, P(.001) < 0.05). The study therefore, recommended that bad parenting is a major issue that must be addressed quickly to reduce negative wellbeing among children with autism disorder.